Strategi Pengembangan Inovasi Bisnis pada Optik Aletalens untuk Meningkatkan Daya Saing - Patricia Gunadhi, Leony; Sri Ayu Lestari; Danang Kusnanto; Rabhi Fathan Muhammad; Dede Jajang Suyaman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze Optik Aletalens' business innovation development strategy to enhance its competitiveness amidst the increasingly competitive and digitalized optical industry. The research method used was a qualitative approach with a descriptive case study design. Data collection techniques included in-depth interviews, direct observation, and documentation. These data were analyzed using thematic analysis and comparative Business Model Canvas (BMC) mapping before and after the innovation development. The results indicate that the innovations implemented included strengthening digital marketing through social media and WhatsApp Business, improving customer experience-based service quality with the support of modern eye examination equipment, and developing partnership strategies and customer loyalty programs that expand market segments and enhance customer interaction. The study's conclusions confirm that an integrated, customer-value-oriented business model transformation can strengthen the value proposition, diversify distribution channels and revenue sources, and build a sustainable competitive advantage for Optik Aletalens. Keywords: Business Model Innovation, Business Model Canvas, Competitiveness, Digital Transformation